Unveiling the Network Properties of Peer Alcohol Network: A Novel Understanding of Alcohol Consumption Behaviour of Adult Network of a Village - Borah, Kimasha; Bhuyan, Kalyan; Sarmah, Ankumon (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Alcohol use disorder is a global phenomenon which has been linked with various kinds of harms including physical, psychological, social, financial and legal harms. The global statistics related to alcohol use, deaths and morbidity associated with alcohol is very alarming which warrants for an effective strategy to deal with the menace of alcohol use. Though apparently alcohol consumption is an individual behaviour, drinking is often influenced by peers. In fact, alcohol consumption is influenced by peers and similarly peer selection is also influenced by alcohol use thus making it a potential area of research from social network analysis (SNA). Therefore, studying the alcohol use from the network theory perspective definitely will shed light on initiation and progression of alcohol use in the community the knowledge of which might be helpful in formulating the strategies to treat and prevent the excessive alcohol use. Hence this study is undertaken to examine the network behaviour and properties of Peer Alcohol Network in a rural area using snowball technique of sampling.